Business recovery: an assessment framework. Issue 3 (6th November 2017) - Stevenson, Joanne R.; Brown, Charlotte; Seville, Erica; Vargo, John
Abstract : This paper presents a Business Recovery Assessment Framework (BRAF) to help researchers and practitioners design robust, repeatable, and comparable studies of business recovery in various post‐disruption contexts. Studies assessing business recovery without adequately considering the research aims, recovery definitions, and indicators can produce misleading findings. The BRAF is composed of a series of steps that guide the decisions that researchers need to make to ensure: (i) that recovery is indeed being measured; (ii) that the indicators of recovery that are selected align with the objectives of the study and the definition of recovery; and, where necessary, (iii) that appropriate comparative control variables are in place. The paper draws on a large dataset of business surveys collected following the earthquakes in Canterbury, New Zealand, on 4 September 2010 and 22 February 2011 to demonstrate the varied conclusions that different recovery indicators can produce and to justify the need for a systematic approach to business recovery assessments.